2014
DOI: 10.1111/ffe.12174
|View full text |Cite
|
Sign up to set email alerts
|

A modified cohesive zone model for a high‐speed expanding crack

Abstract: A B S T R A C T The present work studies a self-similar high-speed expanding crack of mode-I in a ductile material with a modified cohesive zone model. Compared with existing Dugdale models for moving crack, the new features of the present model are that the normal stress parallel to crack faces is included in the yielding condition in the cohesive zone and traction force in the cohesive zone can be non-uniform. For a ductile material defined by von Mises criterion without hardening, the present model confirms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Related theoretical studies have shown that a relatively large FPZ may partially extend beyond the K‐dominant region and lead to significant stress redistribution, with noticeable effects on fracture toughness and fracture angle 10–12 . In general, the cohesive zone model is widely used to characterize the nonlinear fracture characteristics of quasi‐brittle materials 13–17 . In the cohesive zone model, the microcrack in the FPZ is idealized as a cohesive crack and the real crack is regarded as a cohesionless crack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related theoretical studies have shown that a relatively large FPZ may partially extend beyond the K‐dominant region and lead to significant stress redistribution, with noticeable effects on fracture toughness and fracture angle 10–12 . In general, the cohesive zone model is widely used to characterize the nonlinear fracture characteristics of quasi‐brittle materials 13–17 . In the cohesive zone model, the microcrack in the FPZ is idealized as a cohesive crack and the real crack is regarded as a cohesionless crack.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In general, the cohesive zone model is widely used to characterize the nonlinear fracture characteristics of quasi-brittle materials. [13][14][15][16][17] In the cohesive zone model, the microcrack in the FPZ is idealized as a cohesive crack and the real crack is regarded as a cohesionless crack. When the crack tip opening displacement (CTOD) is small, the stress-induced cohesive cracks form the FPZ.…”
Section: Introductionmentioning
confidence: 99%